Surgery Under General Anesthesia Alleviated the Hyperactivity but Had No Effect on the Susceptibility to PND in ADHD Rats - Zhang, Peng; Xu, Feifei; Zhao, Guangchao; Zhang, Xinxin; Li, Ao; Dong, Hailong; Xiong, Lize (Frontiers in Psychiatry, 2019)
Background: Attention-deficit hyperactivity disorder (referred to as ADHD) was a typical neuropsychiatric disorder characterized by inattention, impulsivity and hyperactivity, particularly in children. Recent studies demonstrated a close relationship between the development of ADHD and surgery under general anesthesia. However, few studies illustrated if ADHD symptom changed after surgery. Meanwhile, whether these individuals with natural neural impairment were sensitive to postoperative neurocognitive disorder remained unclear. Methods: SHR rats were utilized as spontaneous ADHD animal model and WKY rats as non-ADHD animal model. We evaluate the variation of neurocognitive function and locomotor activity of the rats undergone the experimental laparotomy with general anesthesia by isoflurane. Neurocognitive function was assessed by Fear Conditioning Test for contextual memory and Morris Water Maze for spatial memory. Depressive like behavior after surgery was detected by Forced Swim Test, and Open Field Test and Elevated Plus Maze Test were utilized to evaluate the locomotor activities and anxiety. Furthermore, we respectively compared EEG signal in ADHD and WKY ratsunder free moving condition. Afterwards, c-Fos staining was also utilized to detect the excitatory of neuron in these rats for exploring the neural mechanism. Results: Locomotor activity of SHR rats assessed by average speed and number of line crossings in Open Field decreased at 1 week after surgery under general anesthesia, but there was no difference concerning anxiety level between SHR rats and WKY rats after surgery. This phenomenon was also paralleled with the change in EEG signal (delta band 0~3 Hz). Surgery under general anesthesia had no effect on the spatial and contextual memory, while it improved the spontaneous depression in SHR rats. The expression of c-Fos was down-regulated for at least 1 weeks in the NAc (nucleus accumbens) area of ADHD rats’ brain after surgery Conclusion: ADHD Rats were not sensitive to postoperative neurocognitive disorder (PND). Surgery with general anesthesia could partly improve the hyperactivity symptom of ADHD rats. This mechanism was related to the suppression of neural activity in cerebral NAc of ADHD rats induced by general anesthetics.